PENERAPAN GROUP INVESTIGATION SEBAGAI ALTERNATIF UNTUK MENGEMBANGKAN SOFT SKILL KERJA SAMA TIM - WIDODO LESTARI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
This Best Practice aims to identify Group Investigation as an alternative solution to develop teamwork soft skills. Working together in a team (Teamwork) is one of the soft skills needed by students as their provision to enter the world of work. This ability must be trained continuously so that these soft skills can become habits and will later become the personality of students because soft skills are attributes and characteristics of a person's personality that affect interpersonal relationships in the workplace. Humans as social beings cannot be separated from their relationships with other humans. One way to develop soft skills in working together in a team (Teamwork) is Group Investigation. This method is a learning model designed to build students' cooperative attitude. The cooperative learning model is a series of learning activities carried out by students in groups to achieve predetermined goals. The results achieved from the application of the group Investigation method are changes in students' attitudes in working together in Teams (Teamwork). ABSTRAKBest Practice ini bertujuan untuk mengetahui Group Investigation sebagai salah satu alternatif solusi mengembangkan soft skill kerja sama dalam tim (teamwork). Bekerjasama dalam Tim (Teamwork) merupakan salah satu soft skill yang diperlukan oleh siswa sebagai bekal mereka untuk memasuki dunia kerja. Kemampuan ini harus dilatih secara terus menerus agar soft skill ini dapat menjadi kebiasaan dan selanjutnya akan menjadi kepribadian dari siswa karena soft skill merupakan atribut dan ciri kepribadian seseorang yang mempengaruhi hubungan Interpersonal ditempat kerja. Manusia sebagai makhluk sosial tidak lepas dari hubungannya dengan manusia lain. Salah satu cara untuk mengembangkan soft skill bekerjasama dalam Tim (Teamwork) adalah Group Investigation. Metode ini merupakan model pembelajaran yang dirancang untuk membangun sikap kooperatif siswa. Model pembelajaran kooperatif merupakan rangkaian kegiatan belajar yang dilakukan oleh siswa dalam kelompok-kelompok untuk mencapai tujuan yang telah ditentukan. Hasil yang dicapai dari penerapan metode group Investigation yaitu perubahan sikap siswa dalam bekerjasama dalam Tim (Teamwork).